EPIDEMICS IN SERBIA DURING THE WARS 1912-1918. : CONTRIBUTION TO VICTIM QUANTIFICATION (Heritage, 2022)
The aim of this paper is to point out the part of different epidemics in the reduction of population in Serbia during the First and Second Balkan Wars (1912 – 1913) and the First World War (1914 – 1918). In addition to suffering on the battlefield, the war conditions of life also led to the culmination of various diseases and the appearance of various major and minor, local, regional and world epidemics. By comparing data from the 1910-1913 census and in 1921 there was a population reduction of 526,430. (4,393,315: 3,866,885). Various infectious diseases took significantly more lives than all other causes combined, including war. According to accepted estimates, during the war years, infectious diseases took about 360,000 lives. The typhus epidemic, which affected the whole of Serbia during the first half of 1915, took about 135,000 lives. This paper is largely based on the analysis of church registers of the dead, and it points out several different local epidemics that affected the Serbian army and civilian population during the war years with great mortal consequences which took about 110,000 lives. These epidemics appeared during the all war years, associated or not associated with each other, and in different territories. These epidemics were: cholera, smallpox, diphtheria, dysentery, scarlet fever, whooping cough, etc.
Keywords: Serbia, The first World War, Epidemic, Disease, Typhoid, Spanish flu, Dysentery, Diphtheria, Cholera, Scarlet fever